Bird Diversity in Ayer Hitam Utara Forest Reserve, Johor and Implications on Peat Swamp Forest Management Strategies - Ahmat, Nur Sakinah; Norazlimi, Nor Atiqah (Journal of Sustainable Natural Resources, 2022)
Ayer Hitam Utara Forest Reserve (AHUFR) is the largest and last existing peat swamp forest in Johor. Peat swamp forest are known to be very important as it serve as a home to variety of flora and fauna, especially the bird species. Other than that, peat swamp forest also prone to forest fire as it become the major threat in Ayer Hitam Forest Reserve during a hot weather or drought (El Nino events). This problem will cause a biodiversity lost and also can threatened the bird’s habitat and behaviour since some birds are extremely susceptible to sudden environmental changes. Therefore, an effective management need to be implemented to the peat swamp ecosystem in order to conserve the forest as well as the bird species that inhabit the area. Hence, this study was conducted to provide a preliminary checklist of the bird, while identify the threats faced by AHUFR in order to came out with the best management of peat swamp forest to protect the bird and the wildlife in it. The method used in this study are mist-netting, direct observation with the aid of DSLR camera, video camera, binocular, and spotter scope, sound recording and interview with forest ranger for four days. About 15 species was recorded, 5 species from direct observation and interview method, 3 species from sound recording, and 2 species from mist-netting method. From the data, one species of vulnerable (VU) and near threatened (NT) species was recorded which are Black Hornbill (Anthracoceros malayanus) (VU) and Fluffy-backed Tit-babbler (Macronus ptilosus) (NT) in which both are native to peat swamp forest. In term of threat, forest fire was identified as common problem usually occurred in AHUFR. The bird diversity in AHUFR can be threatened by the forest fire if there is no action or management taken to mitigate this disturbance from various parties as well as spreading the awareness among the communities according to this issue. Therefore, this study suggested few recommendations of best practices to manage peat swamp forest of AHU based on previous study.